Origin of magnetic anomalies below the neel temperature in nanocrystalline LuMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Rare earth manganites crystallize in distorted orthorhombic perovskite or hexagonal structures and exhibit quite interesting optical and magnetic properties dictated by the size of the rare earth ion. Many of these materials might exhibit both ferroelectric and magnetic ordering as well as magnetoelectric coupling. However, their physical properties at reduced particle sizes remain underexplored due to the challenges associated with their synthesis with a proper control over the crystalline phase. Here, we report the wet-chemical synthesis of the hexagonal phase of nanocrystalline LuMnO3 with an average crystallite size of similar to 32 nm. The room-temperature Raman spectroscopy data are consistent with the calculated values of isomorphous hexagonal RMnO3 (R = rare earth atom) compounds with P6(3)cm symmetry. The UV-vis-NIR spectra recorded in the diffused reflectance mode at room temperature show electronic transitions at 1.7 eV (729 nm), 2.3 eV (539 nm), and 5 eV (258 nm). The magnetization measurements show that the Neel temperature for the LuMnO3 is situated at around 89 K, which is in close proximity to the reported value of the bulk phase. We also observed two unique and field-dependent magnetic anomalies that were predicted earlier but never reported experimentally. The first anomaly is observed as a sharp bifurcation in the ZFC-FC curves below 44 K at a 100 Oe applied field, which is accompanied with a sudden rise in the coercivity and magnetization. A second transition is observed at 12 K as a sharp peak in the ZFC curves, which is accompanied with a dip in coercivity. We attribute the transition at 44 K to the reorientation of the Mn3+ ions due to the Dzyaloshinskii-Moriya interaction, and the transition at 12 K is explained by weak antiferromagnetic coupling between Mn-O-Mn in the ab plane, which becomes dominant at lower temperatures.